Public and Public Utility Enterprises Restructuring: Statistical and Quantitative Aid for Ensuring Human Resource Sustainability - Mladen Čudanov; Ondrej Jaško; Gheorghe Săvoiu (Amfiteatru Economic Journal, 2012)
This article presents a quantitative approach to restructuring public and public utility enterprises, particularly during downsizing requests. The large number of employees in the public sector can be one of the causes for economic instability at country level. That is particularly visible in the context of the euro zone crisis and economic/political instability in countries like Greece, Portugal, Ireland, Spain and Italy. Our approach is based on the statistical analysis of productivity oscillation and setting of performance standards in public and public utility enterprises based on the aforementioned productivity. Data background is given through job descriptions, organizational charts, salary reports and monthly performance reports, in most cases part of organizational information systems. It is recommended for quantitative data to be analyzed on a monthly basis, during a period of 30 or more months. Our method increases procedural fairness and accuracy, because quantitative, statistical, impartial and objective approach is applied for estimating parameters which could be related to downsizing. However, the application of this method is not limited to downsizing, as during its application in more than 20 public and public utility enterprises it was sometimes applied to increase output or reduce costs not necessarily connected to labour. Although it finally refers to downsizing, this method can provide fairer and more impartial approach than the subjective estimate of employee surplus, and its arbitral distribution within the enterprise.
Keywords: L32; L97; L98; M12; M54; 330; public/public utility enterprises; downsizing; productivity; performance; procedural fairness and accuracy